FUNCTIONAL WRlTING (Authors: A. D. Van Nostrand, C. H. Knoblauch, Peter J. McGuire, and Joan Pettigrew) - Lunsford, Andrea A. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1978)
A. D. Van Nostrand, C. H. Knoblauch, Peter J. McGuire, and Joan Pettigrew. FUNCTIONAL WRlTING. Boston: Houghton Mifflin Company, 1978. 378 pp. $10.00.